Review of fabrication, characteristics, and applications of multi-Scale polymer composites - Sadeghi , Farnaz; Hosseinzadeh, Jalaladdin; Tabebordbar, Masoumeh (Journal of Composites and Compounds, 2024)
This review focuses on the multi-scale polymer composites, their applications, structural characteristics, and manufacturing processes. Using micro or nano-sized particles as fibers, multi-scale composite reinforcements improve the thermal, mechanical, and functional characteristics of polymers in ways that single-scale composites cannot. Several manufacturing procedures are evaluated to attain enough dispersion and significant interfacial adhesion between the reinforcements and the polymer matrix. These are essential for the electronics, automotive, and aerospace sectors to have devices with improved functionality and adaptability. Along with the sustainable design issues that multi-scale polymer composites encounter in order to become high-performance materials, the examination examines interface engineering, scalable production, and property optimization control.